2005
DOI: 10.1038/sj.ejhg.5201433
|View full text |Cite
|
Sign up to set email alerts
|

RAR-related orphan receptor A isoform 1 (RORa1) is disrupted by a balanced translocation t(4;15)(q22.3;q21.3) associated with severe obesity

Abstract: We have identified a family comprising a mother and two children with idiopathic and profound obesity body mass index (BMI) 41 -49 kg/m 2 . The three family members carry a balanced reciprocal chromosome translocation t(4;15). We present here the clinical features of the affected individuals as well as the physical mapping and cloning of the chromosomal breakpoints. A detailed characterisation of the chromosomal breakpoints at chromosomes 4 and 15 revealed that the translocation is almost perfectly balanced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Consequently, one might hypothesize that altered levels or function of ARNTL may contribute to hypertension and type 2 diabetes via mechanisms related to disturbed sleep and mood. In addition, we obtained evidence for association of the promoter and intron 1 region of RORA with depression and sleep disturbances, and this same region has been earlier associated with severe obesity [69]. Thus, these findings may offer one possible molecular mechanism for the association between metabolic syndrome and depressive disorders in general population [70], [71].…”
Section: Discussionsupporting
confidence: 60%
“…Consequently, one might hypothesize that altered levels or function of ARNTL may contribute to hypertension and type 2 diabetes via mechanisms related to disturbed sleep and mood. In addition, we obtained evidence for association of the promoter and intron 1 region of RORA with depression and sleep disturbances, and this same region has been earlier associated with severe obesity [69]. Thus, these findings may offer one possible molecular mechanism for the association between metabolic syndrome and depressive disorders in general population [70], [71].…”
Section: Discussionsupporting
confidence: 60%
“…The deregulation and/or SNPs of Rorα and/or γ in humans have been linked to an increased risk of breast and prostate cancers, colorectal adenocarcinomas, pituitary and thyroid tumors (122, 255260), immune deficiency (261), obesity, insulin resistance, and adipogenesis (262264). The cancer risk of mice lacking Rorα or γ ( Rorα −/− or Rorγ −/− ) has not been carefully studied.…”
Section: The Circadian Genes In Cancermentioning
confidence: 99%
“…In humans, two studies have revealed a connection between RORα, obesity, and type 2 diabetes. A rearrangement resulting in disruption of human RORα1 was found to be associated with severe obesity (Klar et al, 2005), while a recent GWAS study showed an association between a single nucleotide polymorphism in RORα (rs7164773) and increased risk for type 2 diabetes in the Mexico Mestizo population (Gamboa-Melendez et al, 2012). …”
Section: Rorα and Insulin Resistancementioning
confidence: 99%